Listening-based Communicative Instructional Approach at the Indonesian Gigantic Immersive Environment - Widya Rizky Pratiwi (Jurnal Pendidikan Humaniora, 2022)
Abstract: Creative Innovation in teaching critically influences students' success. This paper investigates teachers' teaching methods in an Indonesian gigantic English immersive Environment. The qualitative study, which involved eight participants, was conducted in a "let's speak class" at Mr. Pepsi Upgrade, Kampung Inggris Pare, Kediri. Data were gained from classroom observation, interviews, photos, and documents. They were analyzed in six stages, from preparing the data to interpreting the description meaning. Findings promote that teachers teach using technology, like a listening-based communicative instructional approach (L-CIA mode). Six phases were trained, from giving ice breaking to singing together. It stimulates the students' speaking skills.Abstrak: Inovasi Kreatif dalam mengajar sangat mempengaruhi keberhasilan siswa. Artikel ini menginvestigasi metode pengajaran guru dalam Lingkungan imersif Inggris yang sangat besar di Indonesia. Kajian kualitatif yang melibatkan delapan partisipan ini dilakukan dalam sebuah "kelas ayo berbicara" di Mr. Pepsi Upgrade, Kampung Inggris Pare, Kediri. Data diperoleh dari observasi kelas, wawancara, foto, dan dokumen. Mereka dianalisis dalam enam tahap, mulai dari menyiapkan data hingga menafsirkan makna deskripsi. Temuan mempromosikan bahwa guru mengajar menggunakan teknologi, seperti pendekatan pembelajaran komunikatif berbasis mendengarkan (mode L-CIA). Enam fase dilatih, mulai dari ice breaking hingga bernyanyi bersama. Ini merangsang keterampilan berbicara siswa.